The Disordered Landscape of the 20S Proteasome Substrates Reveals Tight Association with Phase Separated Granules. Issue 21 (8th August 2018) - Myers, Nadav; Olender, Tsviya; Savidor, Alon; Levin, Yishai; Reuven, Nina; Shaul, Yosef
Abstract: Proteasomal degradation is the main route of regulated proteostasis. The 20S proteasome is the core particle (CP) responsible for the catalytic activity of all proteasome complexes. Structural constraints mean that only unfolded, extended polypeptide chains may enter the catalytic core of the 20S proteasome. It has been previously shown that the 20S CP is active in degradation of certain intrinsically disordered proteins (IDP) lacking structural constrains. Here, a comprehensive analysis of the 20S CP substrates in vitro is conducted. It is revealed that the 20S CP substrates are highly disordered. However, not all the IDPs are 20S CP substrates. The group of the IDPs that are 20S CP substrates, termed 20S‐IDPome are characterized by having significantly more protein binding partners, more posttranslational modification sites, and are highly enriched for RNA binding proteins. The vast majority of them are involved in splicing, mRNA processing, and translation. Remarkably, it is found that low complexity proteins with prion‐like domain (PrLD), which interact with GR or PR di‐peptide repeats, are the most preferential 20S CP substrates. The finding suggests roles of the 20S CP in gene transcription and formation of phase‐separated granules.